Efektivitas Media My Confident Book Terhadap Sosial Emosional Anak Usia Dini Di Raudhatul Athfal Al-Muttaqin Karangwuluh Kecamatan Suradadi - Ita Nur Itsna; Yessy Pramita Widodo; Irmayatun Nadila (Malahayati Nursing Journal, 2021)
ABSTRACT : THE EFFECTIVENESS OF THE MEDIA MY CONFIDENT BOOK AGAINST THE SOCIAL AND EMOTIONAL EARLY CHILDHOOD IN RAUDATUL ATHFAL AL-MUTTAQIN KARANGWULUH DISTRICT SURADADI Introduction : Early childhood is an individual that is different, unique and has its own characteristics according to their age stages. At this time the stimulation of all aspects of its development has an important role in the task of further development. social emotional early childhood is a child's learning process, where children can interact with others according to existing social rules, and so that children can control their feelings. The development of social skills is applied, one of which educators can use a learning model with the play method using the My Confident Book media. Purpose : This research was conducted to determine the effectiveness of My Confident Book media on the social emotional development of early childhood in Raudhatul Athfal Al Muttaqin Karangwuluh, Suradadi District. Method : This study used a pre experimental design method with the type of pre test and post test one group design. Data were observed and analyzed using the Wilcoxon Matched Pairs Test (pretest and posttest tests). Result : The social emotional development of early childhood before being given the My Confident Book media was 17.5 and after being given the My Confident Book media it showed an average of 20.2, It can be concluded that there is an effect of My Confident Book media on children's social emotional development and there is a significant difference in P-value 0.00 (α = 0.05) regarding children's social emotional development before and after being given the intervention in the form of My Confident Book media.Conclusion : My Confident Book can be developed as media that can increase social emotional ability of the children.   Keywords: Social Emotional, My Confident Book, Early Childhood INTISARI : EFEKTIVITAS MEDIA MY CONFIDENT BOOK TERHADAP SOSIAL EMOSIONAL ANAK USIA DINI DI RAUDHATUL ATHFAL AL-MUTTAQIN KARANGWULUH KECAMATAN SURADADI Latar belakang : Anak usia dini merupakan individu yang berbeda, unik dan memiliki karakteristik tersendiri sesuai dengan tahapan usianya. Pada masa ini stimulasi seluruh aspek perkembangannya memiliki peran penting untuk tugas perkembangan selanjutnya. Sosial emosional anak usia dini merupakan proses belajar anak, dimana anak dapat berinteraksi dengan orang lain sesuai dengan aturan sosial yang ada, dan agar anak mampu mengendalikan perasaannya. Perkembangan keterampilan sosial emosional pada anak usia dini terdapat banyak metode dan teknik yang dapat diterapkan, salah satunya pendidik dapat menggunakan model pembelajaran dengan metode bermain dengan menggunakan media My Confident Book. Tujuan : Penelitian ini dilakukan untuk mengetahui efektivitas media My Confident Book terhadap perkembangan sosial emosional anak usia dini di Raudhatul Athfal Al Muttaqin Karangwuluh Kecamatan Suradadi.Metode : Penelitian ini menggunakan metode pre experimental design dengan jenis pre test and post test one group design. Data diobservasi dan dianalisa menggunakan Wilcoxon Matched Pairs Test (uji pretest dan posttest).Hasil : Perkembangan sosial emosional anak usia dini sebelum diberikan media My Confident Book adalah 17,5 dan setelah diberikan media My Confident Book menunjukan rata-rata 20,2. dapat disimpulkan bahwa ada pengaruh pemberian media My Confident Book terhadap perkembangan sosial emosional anak dan adanya perbedaan yang signifikan P-value 0.00 (α=0.05) tentang perkembangan sosial emosional anak sebelum dan setelah diberikan intervensi berupa media My Confident Book.Kesimpulan : My Confident Book  dapat dikembangkan sebagai media yang dapat meningkatkan kemampuan sosial emosional anak.Kata Kunci: Sosial Emosional, My Confident Book, Anak Usia Dini